Observation of Medium-Induced Yield Enhancement and Acoplanarity Broadening of Low-p_{T} Jets from Measurements in pp and Central Pb-Pb Collisions at sqrt[s_{NN}]=5.02 TeV - Acharya, S; Adamová, D; Aglieri Rinella, G; Agnello, M; Agrawal, N; Ahammed, Z; Ahmad, S; Ahn, S U; Ahuja, I; Akindinov, A; Al-Turany, M; Aleksandrov, D; et al. (Physical review letters, 2024)
The ALICE Collaboration reports the measurement of semi-inclusive distributions of charged-particle jets recoiling from a high transverse momentum (high p_{T}) hadron trigger in proton-proton and central Pb-Pb collisions at sqrt[s_{NN}]=5.02 TeV. A data-driven statistical method is used to mitigate the large uncorrelated background in central Pb-Pb collisions. Recoil jet distributions are reported for jet resolution parameter R=0.2, 0.4, and 0.5 in the range 7<p_{T,jet}<140 GeV/c and trigger-recoil jet azimuthal separation π/2<Δφ<π. The measurements exhibit a marked medium-induced jet yield enhancement at low p_{T} and at large azimuthal deviation from Δφ∼π. The enhancement is characterized by its dependence on Δφ, which has a slope that differs from zero by 4.7σ. Comparisons to model calculations incorporating different formulations of jet quenching are reported. These comparisons indicate that the observed yield enhancement arises from the response of the QGP medium to jet propagation.